The Influence of COSO Organizational Framework Implementation on the Quality of Internal Control in Group of Companies Dani Prisma Mitra (DPM) - Siswo Akhmad Nurhidayat (International Journal of Business Studies, 2018)
This study analyzed the perception of organization members of the group of company in Dani Prisma Mitra (DPM) about the influence of COSO organizational framework consisting of company ethical environments, risk management training and internal audit activities on the quality of internal control procedures. Population in this research is all employee in finance and non-finance department with the level of supervisor and upward at DPM. Hypothesis testing used multiple regression analysis with a discussion of contingency theory. Hypothesis testing concluded that company ethics environments and internal audit activities have the positive and significant influence on the quality of internal control procedure, while risk management activities have a positive but not significant effect on to the quality of internal control procedure.